Pengaruh Tingkat Perputaran Modal Kerja, Leverage, Tingkat Perputaran Kas, dan Pertumbuhan Perusahaan Pada Rentabilitas Ekonomi - Sintya Gita Prabasini, Ketut; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of the level of turnover of working capital, leverage, cash turnover, and company growth on economic rentability in coal mining companies listed on the Indonesia Stock Exchange for the period 2015-2017. The research approach used in this study was a quantitative approach using secondary data. The sampling technique used is non probability sampling with a purposive sampling method. The number of samples used was 54 samples. The analysis technique used is multiple linear regression. Based on the results of the study, this study shows that the variable level of working capital turnover, cash turnover, and company growth has a positive and significant effect on economic rentability while the leverage variable does not have a significant effect on economic profitability. Keywords: Working capital, leverage, cash turnover